2009
DOI: 10.1371/journal.pone.0005903
|View full text |Cite
|
Sign up to set email alerts
|

The Pronounced Th17 Profile in Systemic Sclerosis (SSc) Together with Intracellular Expression of TGFβ and IFNγ Distinguishes SSc Phenotypes

Abstract: BackgroundSystemic sclerosis (SSc) is an autoimmune disease where controversy on Th1/Th2 balance dominates. We investigated whether the recently discovered Th17 pattern was present in SSc.Methodology and Principal FindingsPatients were subdivided as having limited cutaneous SSc (lcSSc, n = 12) or diffuse cutaneous SSc (dcSSc, n = 24). A further arbitrary subdivision was made between early dcSSc (n = 11) and late dcSSc (n = 13) based upon the duration of disease. As a comparator group 14 healthy controls were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 36 publications
7
119
4
2
Order By: Relevance
“…In the study by Komura et al, involving 63 SSc, 15 SLE patients and 31 healthy controls, IL-23 levels were found to be significantly higher in SSc patients compared to SLE patients and healthy controls [13]. In contrast to our study, in a study by Radstake et al, along with increased IL-17 levels in the patient group, had also found IL-23 level and IL-23 receptor expression on CD4+ cells to be higher comparing to the control group was shown in a study by Radstake et al, [14]. In contrast, in a study by Gourh et al on 444 SSc and 216 healthy controls, IL17 and IL23 levels were found to be lower while IL-6, IL-13 ve TNF alpha levels were higher in the SSc group [15].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In the study by Komura et al, involving 63 SSc, 15 SLE patients and 31 healthy controls, IL-23 levels were found to be significantly higher in SSc patients compared to SLE patients and healthy controls [13]. In contrast to our study, in a study by Radstake et al, along with increased IL-17 levels in the patient group, had also found IL-23 level and IL-23 receptor expression on CD4+ cells to be higher comparing to the control group was shown in a study by Radstake et al, [14]. In contrast, in a study by Gourh et al on 444 SSc and 216 healthy controls, IL17 and IL23 levels were found to be lower while IL-6, IL-13 ve TNF alpha levels were higher in the SSc group [15].…”
Section: Discussioncontrasting
confidence: 92%
“…Komura K et al, found higher IL-23 levels in SSc patients [13]. In another study by Radstake TR et al, found both higher IL-17 and IL-23 levels in SSc patients [14]. However, IL-17 and IL-23 levels were determined higher in healthy controls compared to SSc patients in some studies [15].…”
mentioning
confidence: 96%
“…Furthermore, IL-17 overproduction significantly correlated with an early disease stage and an enhanced proliferation of fibroblasts and IL-1 production in SSc patients [39]. Altered IL-17 expression in SSc has also been reported elsewhere, with studies documenting a decrease in regulatory T-cell (Treg) levels, as well as a functional deficiency, accompanied by an increase in CD4+CD25+FoxP3+ T-cells and IL-17 levels, potentially causing an immune imbalance between Treg and Th17 cells [40,41].…”
Section: Interleukin-17supporting
confidence: 52%
“…More recently, Radstake et al described increase levels of activated CD4 + cells in SSc patients compared to healthy controls and CD4 + lymphocytes (activated or not) highly expressed the IL23R, which was associated with a higher IL-17 expression. They also observed increased levels of IL-6, IL-23 and IL-1 cytokines in SSc patients, which all induced IL-17 production (Radstake et al 2009). Furthermore, IL-21 cytokine, which is mainly produced by Th17 and NK cells, potentiates Th17 inflammatory response via stimulation of IL-23 receptor expression and Treg inhibition.…”
Section: Th17 Involvement In Inflammation and Fibrosismentioning
confidence: 95%